Characterization of lignin enforced tannin/furanic foams. Issue 1 (January 2020) - Varila, Toni; Romar, Henrik; Luukkonen, Tero; Hilli, Tuomo; Lassi, Ulla
Abstract: Worldwide, tons of lignin is produced annually in pulping plants and it is mainly considered as a waste material. Usually lignin is burned to produce energy for the pulping reactors. The production of value-added materials from renewable materials like lignin, has proved to be challenging. In this study, the effects of addition of three different types of lignin in the production of tannin/furanic foams is investigated. The foams were matured, first at 373 K and finally carbonized at 1073 K and the properties of them including mechanical strength, specific surface area and pore development are investigated before and after thermal treatment. According to the results, higher mechanical strength is obtained if samples are carbonized at 1073K compared to matured ones at 373K. Up to 10 times stronger materials are achieved this way, which makes them promising as insulating or constructive materials. With physical activation, it is possible to obtain specific surface areas and pore volumes close to 1200 m 2 /g and 0, 55 cm 3 /g respectively. Mainly micropores are developed during the steam activation which makes these foams more suitable and selective to be used as catalyst support materials in the catalytic conversion of small molecules or in adsorption or gas storage application. Abstract : Materials chemistry; Organic chemistry; Lignin, Tannin, Mechanical strength, Physical activation, Pore development